2021
DOI: 10.3389/fmicb.2020.617800
|View full text |Cite
|
Sign up to set email alerts
|

Caeca Microbial Variation in Broiler Chickens as a Result of Dietary Combinations Using Two Cereal Types, Supplementation of Crude Protein and Sodium Butyrate

Abstract: The intestinal microbiome can influence the efficiency and the health status of its host’s digestive system. Indigestible non-starch polysaccharides (NSP) serve as substrates for bacterial fermentation, resulting in short-chain fatty acids like butyrate. In broiler’s nutrition, dietary crude protein (CP) and butyrate’s presence is of particular interest for its impact on intestinal health and growth performance. In this study, we evaluated the effect on the microbial ecology of the ceca of dietary supplementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 47 publications
0
18
0
1
Order By: Relevance
“…This was consistent with many previous studies suggesting that Firmicutes and Bacteroidetes made up the majority of the microbial communities in chickens (accounting for >80%) at the phylum level, and these bacteria affected energy production and metabolism ( Shang et al, 2018 ; Herrero-Encinas et al, 2020 ). Bacteroidetes and Firmicutes were the common colonizers of the chicken intestinal, which were considered to be potentially beneficial autochthonous bacteria ( Borda-Molina et al, 2020 ). Cui et al (2021) found that these two kinds of a dominant phylum of the gut community played an important role in improving intestinal diseases, inhibiting the proliferation of harmful intestinal bacteria, and producing short-chain fatty acids, which reduced luminal pH and regulated the microbial composition (stimulating the growth of beneficial bacteria, such as Bifidobacterium ) ( Dong et al, 2017 ; Ratajczak et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with many previous studies suggesting that Firmicutes and Bacteroidetes made up the majority of the microbial communities in chickens (accounting for >80%) at the phylum level, and these bacteria affected energy production and metabolism ( Shang et al, 2018 ; Herrero-Encinas et al, 2020 ). Bacteroidetes and Firmicutes were the common colonizers of the chicken intestinal, which were considered to be potentially beneficial autochthonous bacteria ( Borda-Molina et al, 2020 ). Cui et al (2021) found that these two kinds of a dominant phylum of the gut community played an important role in improving intestinal diseases, inhibiting the proliferation of harmful intestinal bacteria, and producing short-chain fatty acids, which reduced luminal pH and regulated the microbial composition (stimulating the growth of beneficial bacteria, such as Bifidobacterium ) ( Dong et al, 2017 ; Ratajczak et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The responses obtained in association with these families confirm the impact of the intestinal microbiota on feed digestion and assimilation. Species of the family Bacteroidaceae have a large genome, which favors their adaptation to different environmental factors [ 17 ]. In our study, this family was affected by 10RJ and bacitracin, indicating their responsiveness to gut environmental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…An important section in the gastrointestinal tract is the cecum, in which most fermentation occurs, with a strong influence on intestinal health and animal nutrition. Intestinal fermentation products such as short-chain fatty acids (SCFA) represent an essential contribution of cecal microorganisms to host metabolism and have positive effects on gut health [ 17 ]. The activities of Ruminococcus, Streptococcus, Faecalibacterium, Lactobacillus and Clostridium clusters IV, XIVa and XIVb increase host assimilation of complex substrates by converting them partly to SCFA including butyrate [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore of great metabolic importance. Microbiota of this part of intestine shows metabolic activity ensured by intestinal bacteria (including Ruminococcus , Streptococcus , Faecalibacterium , Lactobacillus , and Clostridium ), which support fermentation processes and produce short-chain fatty acids (SCFA) (e.g., butyrate) [ 44 ]. Chickens have paired cecals, which are habitat for similar bacterial communities.…”
Section: Discussionmentioning
confidence: 99%